Experimental Analysis of Planet Carrier Bearing Loads under Torque and Bending Moment in a Four-Point-Suspension Drive Train. Issue 3 (1st May 2022) - Krause, A; Gnauert, J; Jacobs, G; Bosse, D; Schmitz, L
Abstract: Bearing failures in wind turbine gearboxes still occur which results in downtimes and hence leads to an increase in the levelized cost of energy. One of these affected bearings are the planet carrier bearings as they are still subject to unexpected fatigue related failure modes, like pitting and spalling, which are mainly influenced by the load distribution in the bearing. Hence it is necessary to determine the influence of torque and bending moment loads onto the planet carrier bearings. In this work the generator sided planet carrier bearing load distribution is investigated. Therefore, strain gauges are applied onto the circumference of that bearing of the gearbox of a 1 MW wind turbine four-point-suspension drive train. The loading is measured while testing at the 4 MW wind turbine test bench at CWD. The relevant loading for the investigated generator sided planet carrier bearing is torque which leads to a tilting of the gearbox leading to two load zones in the bearing. Bending moments at the hub of the drive train do not influence the bearing load distribution as they are absorbed by the main bearing.